QSAR, chalcones derivatives, tum Quantitative structure-activity relationship studies of series of chalcones derivatives as inhibitors of tumor necrosis factor-alpha - Alhassan, Wisam; Sadiq M. H. Ismae; Jasim M. Al-Shawi (Al-Qadisiyah Journal of Pure Science, 2020)
Quantitative structure-activity relationship (QSAR) teqnique was used to predict the biological activity of a series of chalcones compounds as anti-inflammatory. 26 physicochemical descriptors are tested in QSAR equations configuration to predict biological effectiveness of compounds under study. The values of R2 in Eqs (1–3) ranged from 0.794–0.873, the F values ranged from 14.161–26.206 and the S values ranged from 0.262–0.334. The results demonstrated excellent models based on Eq.3, along with high of R2, F and minimum S by employing three parameters r(C3-C5), (LUMO+1) and (LUMO+2). This signifies that these parameters play a significant role in determining anti-inflammatory characteristics.